Aggregation behavior and reproductive compatibility in the family Cimicidae - DeVries, Zachary; Mick, Russell; Balvín, Ondřej; Schal, Coby (Scientific reports, 2017)
Bed bugs (Cimex lectularius) provide a unique opportunity to understand speciation and host-associated divergence in parasites. Recently, two sympatric but genetically distinct lineages of C. lectularius were identified: one associated with humans and one associated with bats. We investigated two mechanisms that could maintain genetic differentiation in the field: reproductive compatibility (via mating crosses) and aggregation fidelity (via two-choice sheltering assays). Effects were assessed at the intra-lineage level (within human-associated bed bugs), inter-lineage level (between human- and bat-associated bed bugs), and inter-species level (between C. lectularius and Cimex pipistrelli [bat bug]). Contrary to previous reports, bed bugs were found to be reproductively compatible at both the intra- and inter-lineage levels, but not at the inter-species level (although three hybrids were produced, one of which developed into an adult). Lineage- and species-specific aggregation fidelity was only detected in 8% (4 out of 48) of the aggregation fidelity assays run. These results indicate that under laboratory conditions, host-associated lineages of bed bugs are reproductively compatible, and aggregation pheromones are not capable of preventing gene flow between lineages.
Keywords: Reproduction; tok genů; rozdělení chí kvadrát; Animals; Behavior, Animal; rozmnožování; Bedbugs; Chi-Square Distribution; Female; Gene Flow; chování zvířat; zvířata; mužské pohlaví; Male; štěnice; ženské pohlaví